Knowledge, Technology Transfer and Foresight
XVII, 250 p.
Keywords: A comparative perspective on the problems and issues of the transfer of knowledge and technology in and between western and former socialist countries, focusing on three key technologies: laser technology, biotechnology, and information technology. The book highlights the specific challenges facing economies in transition in technology policy and commercialisation. Furthermore, it gives an excellent insight into current technology forecasting practice and methodology, and the use of forecasting results in framing science and technology policy. Audience: Those involved in science and technology policy and forecasting, such as industrial and governmental policy makers and researchers.